Scandium fluorophosphate glasses: a structural approach - Nalin, Marcelo [UNESP]; Ribeiro, SJL; Messaddeq, Younes [UNESP]; Schneider, J.; Donoso, P. (Elsevier B.V., 2002)
A systematic investigation on glass formation in the ternary system InF3-BaF2-[Sc(PO3)(3)](n) has been carried out. Scandium polyphosphate [Sc(PO3)(3)](n) has been used as a third component in order to investigate the possibilities of obtaining new stable glasses. The above long-chain polyphosphate has been prepared using a specially elaborated cryo-technique, which allowed the preparation of high-purity product. Stable ternary compositions have been obtained within the compositions range (in mol%): 5-75 InF3, 0-80% BaF2, 0-50% [Sc(PO3)(3)](n). Glasses were characterized by Differential Scanning Calorimetry, vibrational spectroscopy (Raman) and P-31 NMR. Structural features for the glass were put forward. Isolated P(O,F)4 groups or fluoroindated metaphosphate units could be identified depending on glass compositions. (C) 2002 Academie des sciences / Editions scientifiques et medicales Elsevier SAS.
Keywords: fluorophosphate; scandium polyphosphate; Raman; P-31 RMN